DETERMINATION OF INDICATORS OF THE DETERIORATION OF THE EPIDEMIOLOGICAL AND EPIZOOTOLOGICAL SITUATIONS - Sikhayeva , N.S.; Zakarya , K.D.; Adilova , A.A.; Zhubanova , G.S.; Zharmuhambetova , D.T.; Abeldinova , A.S.; Abdybekova , A.M.; Rsaliev , A.S. (Eurasian Journal of Applied Biotechnology, 2023)
Major outbreaks of infectious diseases have demonstrated the need for new approaches to biosecurity, which include efficient planning and implementation of infection prevention and control measures. This work is not possible without the early determination of relevant indicators. The purpose of the work is the analysis of indicators in determining the deterioration of the epidemiological and epizootological situation. Results. The methodological approaches to the collection of information, the definition of indicators and their evaluation were analyzed. The analysis of the role of indicators in assessing the epidemiological and epizootological situation in terms of diseases was carried out. The main indicators of the deterioration of the epidemiological and epizootological situation for such diseases as coronavirus infection, anthrax, brucellosis, and plague have been identified. Conclusion. The following three general indicators assessing the deterioration of the epidemiological situation were identified: an increase in the incidence, a decrease in the coverage of preventive vaccinations, and the ignition of dormant foci of diseases. To assess the epizootic situation, additional indicators were identified, such as an increase in the incidence in animal population and changes in natural, climatic and soil conditions. Indicators of deterioration of the epidemiological situation may vary depending on the specific disease and its mode of transmission.